EFEK PEMBERIAN KOMBINASI GARAM DAPUR DAN PUPUK NITROGEN TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasilliensis Muell.Arg.) DI POLIBAG - Nasamsir Nasamsir (Universitas Batanghari Jambi, 2013)
An experiment was conducted to study the influence of table salt (NaCl) and nitrogen fertilizer (Urea) at different dosages in growth increasing the Hevea seedling in Pattimura street, Jambi, from 5 July to 5 September 2013. Hevea seedling (PB 260) was grown in polyethylene bag.The experiment was carried out in completely randomized design with 3 replications. NaCl treatments arranged in five levels that is ; 0,0 g, 12,5 g, 8,5 g, 24,5 g, and 30,5 g. NaCl solution was poured to the medium surface 10 days after planting. Nitrogen fertilizer consist of four levels, i.e. ; 0,0 g, 7,0 g , 14,0 g , and 21,0 g. The fertilizer was given in three steps ; 5 , 30, and 60 days after planting. This three steps had the same urea weight. Response variable was SRR, RGR, and NAR from 14 to 70 days after planting.The experirnent result showed that NaCl effects interaction with nitrogen effects in SRR, RGR, and NAR. NaCl with nitrogen treatments could cause the increase of SRR, RGR, and NAR.The giving of 30,5 g NaCl with 7 – 14 g urea showed the highest SRR, RGR, and NAR , it was not differernt on application 24,5 g NaCl.Key words ; Hevea seedling (PB 260) , NaCl, Urea, SRR, RGR, NAR